USING FAIRY TALES IN TEACHING ENGLISH TO YOUNG LEARNERS - D.B.Kayumov; Xursanova Karina Timurovna (TADQIQOTLAR, 2026)
Abstract This article explores the effectiveness of integrating fairy tales into English language instruction for young learners. It highlights the benefits of using familiar narratives to enhance language acquisition, stimulate imagination, and promote cultural understanding. The article discusses various strategies for incorporating fairy tales into lesson plans, such as storytelling, role-playing, and creative writing activities. Additionally, it addresses the cognitive and emotional development of children through engagement with these timeless stories. The article concludes with practical tips for educators on how to select appropriate fairy tales and adapt them to suit different learning levels.